Fertility Changes and Replacement Migration - Yunus Aksoy; Gylfi Zoega (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study OECD countries that differ in immigration policies but share a high level of human capital. We find significant negative statistical relationship between 16 years lagged fertility and the rate of immigration in a panel of 23 countries, which indicates that immigration compensates for low fertility in the labor market.
Keywords: J13; J61; 330; fertility; replacement migration